Launching the Imagination - Mary Stewart (McGraw-Hill Education, 2011)
Author, artist, and educator Mary Stewart is the Foundations Program Director for the Art Department at Florida State University and co-founder of Integrative Teaching Thinktank, a national organization devoted to strengthening college-level teaching. She regularly gives workshops and lectures on creativity, curriculum design, visual communication, leadership and visual narrative. Her artwork has been shown in over eighty exhibitions nationally and internationally, and she has received two Pennsylvania Council on the Arts grants for choreography. She received the FATE (Foundations in Art: Theory and Education) Master Educator award and the National Council of Arts Administrators Award of Distinction in 2009.